Persepsi dan Preferensi Pengunjung Terkait Pengalaman di Kawasan Wisata Kuliner Dusun Pronosutan - Dzaki, Amirul Naufal; Setiawan, Bakti (ATRIUM: Jurnal Arsitektur, 2025)
Title: Visitor Perceptions and Preferences Regarding Visitor Leisure Experiences in the Culinary Area of Dusun Pronosutan This study discusses visitors' motivations to Pronosutan, Kembang Village, which has experienced rapid tourism growth after the COVID-19 pandemic. The revenge tourism trend increases the need for outdoor recreation and relaxation. This area initially had no tourism potential but began to develop with the emergence of culinary spots such as Geblek Pari, Geblek Menoreh View, and Mahaloka Paradise. This study explores visitor perceptions and preferences towards the tourism experience at Pronosutan View, which is known through social media for its natural beauty and rural atmosphere. With qualitative exploratory methods, the study found that natural beauty, place atmosphere, and culinary are the main factors that influence visitor perceptions and preferences. In exploring visitor preferences and perceptions of visitor experiences, focusing on activity factors influencing leisure experiences and visitor decisions in tourist destinations, leisure is another meaning in relaxation and recreation activities. Relaxing leisure activities, such as taking pictures, relaxing, and enjoying the countryside, are the main attractions. Research also shows that visitors choose destinations based on the relaxation and recreation experiences they offer. Pronosutan has excellent potential to become an attractive tourist destination by emphasizing a relaxed leisure experience and enjoying the natural atmosphere of Pronosutan's countryside.